Focus Strategy of Business Products Through Competitive Performance - Surapto, Deni (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Based on year-on-year growth, Indonesia’s economic growth in the first quarter of 2020 was largest in the information and communication sector, namely 0.53% through the use of the digital economy which plays an important role in supporting the economy through the downstreaming of information technology. The important role of Micro, Small and Medium Enterprises (MSMEs) as contributors to Gross Domestic Product in the recovery of the Indonesian economy, the government is committed to continuing to support MSMEs so that they can survive, develop and grow amidst the crisis. pandemic challenges and transformation through the National Economic Recovery Program (NoF 2021). Jayapura Province recorded significant progress in terms of the growth of cooperatives and SMEs in supporting government programs with 944 business units spread across 20 districts and cities (Papua.go.id) followed by an increase in regional income and alleviating poverty in the region. Quantitative methodology with a sample size of 110 SMEs using 5 Likert scales. The analysis tool uses SEM PLS. The results of this research show that there is a significant positive influence between growth strategy, focus strategy, technology selection on competitive performance.